Wear-resistant PVC electric power pipe and preparation method thereof

By adopting a multi-layer structure design, wear-resistant PVC power pipes, using high-performance materials and modified fillers, the shortcomings of traditional power pipes in material compatibility, mechanical properties and wear resistance are solved, and higher strength is achieved , stability and wear resistance, suitable for complex environments.

CN119408257APending Publication Date: 2025-02-11KANGMINGYUAN GUIZHOU SCI & TECH DEV CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411484992.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Traditional PVC power tubes have shortcomings in material compatibility, mechanical properties, wear resistance, chemical stability and environmental protection, and are difficult to meet the growing application needs.

Method used

Wear-resistant PVC power tube designed with multi-layer structure, the outer wear-resistant layer consists of high-performance materials such as polyethylene, polyether ether ketone, polyurethane, mixed fibers and nanoboronitride. The inner tube layer contains modified fillers and composites. Thermal stabilizer and mixed silane coupling agent ensure the uniformity and binding force of each component through precise preparation process and monitoring system control.

Benefits of technology

It significantly improves the strength, stability, wear resistance, mechanical properties and chemical stability of the power tube, extends the service life, and the material is environmentally friendly and non-toxic, and is suitable for complex working environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098493120000121
    Figure BDA0005098493120000121
  • Figure BDA0005098493120000131
    Figure BDA0005098493120000131
Patent Text Reader

Abstract

The invention relates to a wear-resistant PVC electric tube and a preparation method thereof. The power pipe comprises an outer wear-resistant layer and an inner pipe layer, and the performance is improved through an innovative preparation mode. A novel compatilizer preparation method is adopted, so that the compatibility of the material is improved; a silane coupling agent is mixed to enhance the binding force between the filler and the resin; the combination of the composite heat stabilizer and the dispersant ensures the heat stability and dispersion uniformity. The multi-layer structural design plays the advantages of different materials. The material has the advantages of excellent wear resistance, favorable mechanical properties, excellent chemical stability, environment friendliness, no toxicity and favorable processability. According to the preparation method, process parameters are accurately controlled, and an advanced monitoring system is adopted, for example, an acquisition module is arranged to acquire comprehensive data, a data processing module analyzes data, and a control module adjusts the preparation process. The electric power tube has wide application prospects in the fields of electric power, communication and the like, can meet the use requirements of complex environments, and provides reliable product support for development of related industries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electric power pipes, and in particular to a wear-resistant PVC electric power pipe and a preparation method thereof. Background Art

[0002] In the current power industry, traditional PVC power pipes have many problems and are difficult to meet the growing application needs. Traditional power pipes perform poorly in terms of material compatibility. Due to the lack of effective compatibilizers, the combination of different materials is not tight enough, resulting in insufficient strength and stability of the pipes, and the overall performance is difficult to achieve ideal conditions.

[0003] In terms of the use of additives, the traditional electric power pipes use only a single silane coupling agent, which cannot fully enhance the bonding force between the filler and the resin, limiting the improvement of mechanical properties and wear resistance. At the same time, the combination of heat stabilizers and dispersants is not ideal, making it difficult to ensure thermal stability during processing and the uniformity of dispersion of each component, affecting the quality and performance of the pipe.

[0004] In terms of structural design, traditional power pipes are usually of a single structure, which cannot fully utilize the advantages of different materials and is difficult to simultaneously meet the requirements of wear resistance, insulation and mechanical properties.

[0005] In terms of characteristics, traditional power pipes have poor wear resistance, are difficult to effectively resist external wear and scratches, and have a short service life. In terms of mechanical properties, they are insufficient in compression, tension and bending resistance, weak in impact resistance, and are easily damaged by external impact during installation and use. Chemical stability also needs to be improved, and the resistance to chemical substances such as acids, alkalis, and salts is limited, and they are easily corroded in complex working environments. In addition, traditional power pipes also have deficiencies in environmental protection and processing performance. Some materials may be toxic and harmful, causing harm to the environment and human health, and the fluidity and processability during the processing are poor, making it difficult to prepare pipes of various shapes and sizes.

[0006] In the preparation process, the traditional methods do not have precise enough control over parameters such as temperature, time, and rotation speed, and lack advanced monitoring systems, which leads to low precision and efficiency in the composite process, making it difficult to ensure stable quality and reliable performance, and is not conducive to large-scale production.

[0007] In summary, in order to solve these problems of traditional PVC power pipes, the present invention discloses a wear-resistant PVC power pipe and a preparation method thereof. Summary of the invention

[0008] In view of the deficiencies of the prior art, the technical solution adopted by the present invention to solve the technical problems is: a wear-resistant PVC power pipe, the power pipe comprises an outer wear-resistant layer and an inner pipe layer, the outer wear-resistant layer formula comprises the following components by weight: 15-20 parts of polyethylene, 60-70 parts of polyetheretherketone, 10-20 parts of polyurethane, 25-25 parts of mixed fiber, 12-15 parts of nano boron nitride, 3-5 parts of silane coupling agent, 1-2 parts of graphite nanosheet lubricant, and 1-3 parts of calcium zinc stabilizer;

[0009] The inner tube layer comprises the following components by weight: 80-90 parts of PVC resin, 16-20 parts of modified filler, 24-26 parts of ethylene-vinyl acetate copolymer, 3-4.5 parts of composite heat stabilizer, 2-3 parts of dispersant, 1.1-1.4 parts of lubricant, 4-5 parts of mixed silane coupling agent, 1.5-2.5 parts of plasticizer, 2-2.6 parts of antioxidant, 3-6 parts of compatibilizer, and 6-8 parts of wear-resistant filler;

[0010] The specific preparation method of the compatibilizer is as follows:

[0011] Step A1: dissolve PVC in tetrahydrofuran, add the solution into a four-necked flask equipped with a stirring device, a thermometer, a reflux condenser and a nitrogen protection device, slowly add a mixture of styrene and acrylic acid into the four-necked flask, and stir evenly;

[0012] Step A2: Add initiator BPO and antioxidant into a four-necked flask, raise the temperature to 70-90°C under nitrogen protection, and react for 3-5 hours;

[0013] Step A3: After the reaction is completed, cool to room temperature, pour the product into methanol for precipitation, remove unreacted monomers, initiators and solvents, filter the precipitate, wash it repeatedly with methanol, and then dry it in a vacuum drying oven to constant weight to obtain a styrene-acrylic acid copolymer grafted polyvinyl chloride compatibilizer.

[0014] Preferably, the amount of the initiator BPO is 0.5%-2% of the total mass of PVC, styrene and acrylic acid, and the molar ratio of styrene to acrylic acid is 2:1-4:1.

[0015] Preferably, the mixed silane coupling agent is formed by mixing vinyl triethoxy silane coupling agent and γ-aminopropyl triethoxy silane coupling agent in a ratio of 3:2, and the plasticizer is formed by mixing epoxy soybean oil and dioctyl terephthalate in a ratio of 2:1.

[0016] Preferably, the composite heat stabilizer is a calcium-zinc composite heat stabilizer, and the dispersant is a mixture of EBS and polyethylene wax in a ratio of 1:1.

[0017] Preferably, the specific preparation method of the modified filler is as follows:

[0018] Step B1: vacuum drying the nano boron nitride at 120°C for 10 hours, adding the silane coupling agent KH580 to a mixed solution of ethanol and water, wherein the volume ratio of ethanol to water is 9:1, adjusting the pH value of the solution to 5, and then stirring the reaction at 70°C for 2 hours;

[0019] Step B2: adding the dried nano boron nitride to the hydrolyzed silane coupling agent solution, stirring and reacting at 80° C. for 6 hours;

[0020] Step B3: Filter and wash the product after the reaction, and then vacuum dry it at 80° C. for 12 hours to obtain a modified filler after the nano-boron nitride is modified by a silane coupling agent.

[0021] A method for preparing a wear-resistant PVC power pipe comprises the following preparation steps:

[0022] Step S1: prepare the outer wear-resistant layer in advance, mix basalt fiber, aramid fiber, glass fiber and carbon fiber in proportion, put them into a vacuum drying oven, dry them at 90°C for 6 hours, put nano boron nitride into a vacuum drying oven at 135°C for 10 hours, and sieve polyethylene, polyetheretherketone and polyurethane respectively;

[0023] Step S2: adding the treated polyethylene, polyetheretherketone, and polyurethane into a high-speed mixer, setting the speed to 650 rpm, mixing for 15 minutes, slowly adding the treated mixed fiber, nano boron nitride, silane coupling agent KH580, graphite nanosheet lubricant, and calcium zinc stabilizer, wherein the mixed fiber is composited by basalt fiber, aramid fiber, glass fiber, and carbon fiber in a ratio of 1:1:1:1, continuing to mix at a speed of 700-800 rpm for 30-45 minutes, and extruding using a twin-screw extruder at a temperature of 188°C-228°C to obtain an outer wear-resistant layer;

[0024] Step S3: placing the PVC resin and ethylene-vinyl acetate copolymer in a drying oven and drying them at 70° C. for 5 hours, and drying the modified filler of nano-boron nitride modified by the silane coupling agent in a vacuum drying oven at 115° C. for 8 hours;

[0025] Step S4: adding the dried PVC resin, ethylene-vinyl acetate copolymer, and modified filler into a high-speed mixer, mixing at a speed of 950 rpm for 20-25 minutes, adding a composite heat stabilizer, a dispersant, a lubricant, a mixed silane coupling agent, a plasticizer, an antioxidant, a compatibilizer, and a wear-resistant filler in sequence, and continuing to mix at a speed of 800 rpm for 35 minutes;

[0026] Step S5: adding the mixed materials into an extruder at 168°C-198°C for extrusion to obtain an inner tube layer;

[0027] Step S6: After the outer wear-resistant layer pipe and the inner pipe layer are extruded, cooled and sized, the outer wear-resistant layer pipe is put on the inner pipe layer body, and then the put-on pipe is placed in a heating device. The monitoring system controls the system to heat evenly and slowly raise the temperature to 165°C. A pressure of 0.8-1.2MPa is applied to the pipe, and the pressure and temperature are maintained for 15 minutes. After the compounding is completed, the pipe is taken out of the heating device and naturally cooled to room temperature to obtain a wear-resistant PVC power pipe.

[0028] Preferably, the specific monitoring method of the monitoring system in step S6 is as follows:

[0029] Step 1: Obtain comprehensive data, including temperature, pressure, and dimension data, by setting up an acquisition module. By setting a temperature sensor in the heating device, a pressure sensor at the pipe pressure application point, and a dimension measurement sensor at the position before and after the pipe is compounded, the comprehensive data is obtained in real time and transmitted to the data processing module.

[0030] Step 2: The comprehensive data is transmitted to the data processing module, and the data processing module processes and analyzes the collected data;

[0031] Step 3: After being processed by the data processing module, the result data is obtained, and the control module is controlled by the result data to adjust the preparation process;

[0032] Step 4: Store the original data, comprehensive data and result data by setting a storage module, where the original data includes setting parameters, thresholds and hysteresis interval information;

[0033] Step 4: Visually display the temperature, pressure, size, time, operating status and alarm information by setting the display module;

[0034] Step 5: Use a standard source to periodically calibrate each sensor in step 1 by setting up a calibration module.

[0035] Preferably, the specific steps of processing and analyzing the collected data by the data processing module in step 2 are as follows:

[0036] Step C1: Use mean filtering and median filtering algorithms to remove noise and outliers in the data, filter the data, and obtain preprocessed data;

[0037] Step C2: Check whether the difference between adjacent pre-processed data is within a set threshold. If the temperature difference between two adjacent acquisitions exceeds the set threshold, mark the data to obtain marked data.

[0038] Step C3: By comparing with the comprehensive data of adjacent sensors and combining with historical data trend analysis, determine whether the marked data is abnormal for further verification. If abnormal, record it as abnormal data and no subsequent processing will be performed on the abnormal data.

[0039] Preferably, in step 3, the result data controls the control module, and the specific method of adjusting the preparation process is as follows:

[0040] Step D1: The result data includes pre-processed data, marked data and abnormal data. A real-time database is established for the temperature, pressure and dimension data in the comprehensive data, and the data collected each time and the corresponding timestamp are recorded and stored in chronological order.

[0041] Step D2: continuously record the measured values ​​of the comprehensive data and calculate the difference between adjacent measured values. If the difference is continuously positive or negative, record the trend direction and change rate to obtain its change curve on the time axis and the correlation change trend between the two.

[0042] Step D3: Establish a trend model library to store typical trend models of comprehensive data changing over time during normal production, compare the real-time monitored trends with the trends in the model library, and obtain positive feedback trend deviation information;

[0043] Step D4: Calculate the difference between the actual temperature and the target temperature of 165°C, calculate the difference between the pressure and the set range of 0.8-1.2MPa, calculate the size and compare it with the design error range of ±0.1mm to obtain the deviation value, and establish a deviation impact assessment model in combination with material property data and process requirement data;

[0044] Step D5: Combined with the abnormal data marked by the data processing module, statistical analysis is performed on the data whose difference between adjacent data exceeds one times the threshold value, the degree of abnormality is determined according to the frequency and duration of the abnormal data, and an abnormal data determination rule base is established. When the data meets the abnormal determination rule, it is confirmed as abnormal data as negative feedback deviation and abnormal data information;

[0045] Step D6: Integrate the positive feedback trend deviation information and the negative feedback deviation and abnormal data information, and comprehensively calculate the evaluation value based on the weight distribution principle of each parameter's impact on product quality. If the evaluation value reaches the preset warning threshold, make a warning decision, generate a corresponding warning signal based on the warning type and severity, display the abnormal parameters and recommended measures, and automatically take emergency stop and adjust equipment parameters according to the preset rules. Preliminary response operations, while waiting for further processing by the operator.

[0046] Preferably, in step D3, the specific steps of comparing the real-time monitored trend with the trend in the model library are as follows:

[0047] Step E1: When the monitored trend is inconsistent with the preset normal trend, the trend deviation is calculated;

[0048] Step E2: For the size trend, the deviation is calculated according to the difference between the continuous measurement value fitting curve and the normal trend curve. For the correlation trend between temperature and pressure, the deviation is determined by analyzing the difference between the relationship curve between the two and the normal relationship model.

[0049] Step E3: Set a threshold value according to the deviation size and duration. When the deviation exceeds the threshold value for three consecutive measurements, it is used as a basis for early warning judgment.

[0050] The beneficial effects of the present invention are as follows:

[0051] 1. In terms of performance improvement, a new compatibilizer preparation method is adopted, and a compatibilizer is prepared by grafting styrene and acrylic acid with polyvinyl chloride, which improves the compatibility between different materials. Compared with traditional compatibilizers, it can better promote the combination of various components, improve the strength and stability of the pipe, and thus improve the overall performance of the power pipe. The use of mixed silane coupling agent, vinyl triethoxy silane coupling agent and γ-aminopropyl triethoxy silane coupling agent are mixed in a specific proportion, which enhances the bonding force between filler and resin, and provides a new way to improve the mechanical properties and wear resistance of power pipes. The combination of calcium zinc composite heat stabilizer and EBS and polyethylene wax mixed dispersant not only ensures the thermal stability during processing, but also improves the dispersion uniformity of various components, effectively solves the problems existing in traditional heat stabilizers and dispersants, thereby improving the quality and performance of the pipe. The multi-layer structure design, the outer wear-resistant layer provides wear resistance and protection, the inner pipe layer guarantees insulation and mechanical properties, gives full play to the advantages of different materials, and achieves performance optimization combination, which is innovative in the field of power pipes.

[0052] Second, in terms of characteristic advantages, first of all, the power pipe has excellent wear resistance. The outer wear-resistant layer contains high-performance materials such as polyethylene, polyetheretherketone, polyurethane, mixed fiber and nano boron nitride, which greatly improves the wear resistance of the power pipe and can effectively resist external wear and scratches. At the same time, the wear-resistant filler in the inner tube layer further enhances the overall wear resistance, ensuring that the power pipe can maintain good performance in various harsh environments, thereby extending the service life of the power pipe. Secondly, it exhibits good mechanical properties. Polyetheretherketone has extremely high mechanical strength and high temperature resistance. After compounding with other materials, the power pipe has excellent compression, tension and bending resistance, and can withstand large external forces. Moreover, the addition of mixed fibers enhances the strength and toughness of the pipe, improves its impact resistance, and reduces the risk of damage due to external impact during installation and use. Furthermore, it has excellent chemical stability. PVC resin itself has good chemical corrosion resistance, coupled with various additives in the outer wear-resistant layer and the inner tube layer, so that the power pipe can resist the erosion of various chemical substances such as acid, alkali, salt, etc., and is suitable for various complex working environments. The use of calcium zinc stabilizers and antioxidants improves the stability of the power pipe and prevents it from aging and degradation during long-term use. Finally, it embodies the characteristics of environmental protection and non-toxicity. Most of the materials used in the power pipe are environmentally friendly materials, which are non-toxic and harmless and will not cause harm to the environment and human health. Toxic and harmful solvents and additives are not used in the preparation process of the compatibilizer, which meets environmental protection requirements. At the same time, the good processing performance makes the material formula of the inner tube layer and the outer wear-resistant layer have good fluidity and processability during the processing after careful design, and can be easily prepared into power pipes of various shapes and sizes through processes such as extrusion. The optimization of various process parameters in the preparation method ensures the stable quality of the pipe and improves production efficiency.

[0053] 3. In terms of technological innovation and application prospects, precise control of the preparation process: precise control of parameters such as temperature, time, and rotation speed in each process step to ensure stable quality and reliable performance. The use of advanced monitoring system controls the system to uniformly heat and pressurize, which improves the accuracy and efficiency of the composite process and provides technical support for the large-scale production of power pipes. The wear-resistant PVC power pipe of the present invention has broad application prospects in the fields of electricity, communications, etc., and can meet the use requirements in various complex environments, providing reliable product support for the development of related industries. DETAILED DESCRIPTION

[0054] The present invention is further described in detail below in conjunction with specific embodiments. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

[0055] Embodiment 1: A wear-resistant PVC electric pipe, comprising an outer wear-resistant layer and an inner pipe layer. The outer wear-resistant layer comprises the following components by weight: 18 parts of polyethylene, 65 parts of polyetheretherketone, 15 parts of polyurethane, 25 parts of a mixed fiber composed of basalt fiber, aramid fiber, glass fiber and carbon fiber in a ratio of 1:1:1:1, 13 parts of nano-boron nitride, 4 parts of silane coupling agent, 1.5 parts of graphite nanosheet lubricant and 2 parts of calcium zinc stabilizer.

[0056] After the basalt fiber and other mixed fibers are evenly mixed, they are dried in a vacuum drying oven at 90° C. for 6 hours. The nano-boron nitride is dried in a vacuum drying oven at 135° C. for 10 hours. Polyethylene, polyetheretherketone, and polyurethane are sieved respectively.

[0057] The inner tube layer includes the following components by weight: 85 parts of PVC resin, 18 parts of modified filler, 25 parts of ethylene-vinyl acetate copolymer, 4 parts of composite heat stabilizer, 2.5 parts of dispersant, 1.2 parts of lubricant, 4.5 parts of mixed silane coupling agent, 2 parts of plasticizer, 2.3 parts of antioxidant, 4 parts of compatibilizer and 7 parts of wear-resistant filler.

[0058] Dissolve PVC in tetrahydrofuran and add it to a four-necked flask equipped with a stirring device, a thermometer, a reflux condenser and a nitrogen protection device. Slowly add a mixture of styrene and acrylic acid in a molar ratio of 3:1 into the four-necked flask and stir evenly. Add initiator BPO and antioxidant in an amount of 1.2% of the total mass of PVC, styrene and acrylic acid, heat to 80°C under nitrogen protection, and react for 4 hours. After the reaction is completed, cool to room temperature, pour into methanol for precipitation, filter the precipitate and wash it repeatedly with methanol, and then dry it in a vacuum drying oven to constant weight to obtain a compatibilizer.

[0059] The nano boron nitride was vacuum dried at 120°C for 10 hours, and the silane coupling agent KH580 was added to a mixed solution of ethanol and water in a volume ratio of 9:1, the pH value was adjusted to 5, and the mixture was stirred and reacted at 70°C for 2 hours. The dried nano boron nitride was added to the hydrolyzed silane coupling agent solution, and the mixture was stirred and reacted at 80°C for 6 hours. The reaction product was filtered, washed, and vacuum dried at 80°C for 12 hours to obtain a modified filler.

[0060] The specific preparation method is as follows:

[0061] Add the treated polyethylene, polyetheretherketone and polyurethane into a high-speed mixer at a speed of 650 rpm and mix for 15 minutes. Slowly add the treated mixed fiber, nano boron nitride and other materials and mix at a speed of 750 rpm for 38 minutes. Extrude the outer wear-resistant layer with a twin-screw extruder at a temperature of 208°C.

[0062] The PVC resin and ethylene-vinyl acetate copolymer were dried in a drying oven at 70°C for 5 hours, and the modified filler was dried in a vacuum drying oven at 115°C for 8 hours.

[0063] The dried PVC resin and other materials were added into a high-speed mixer and mixed at 950 rpm for 23 minutes. The composite heat stabilizer and other materials were added in sequence and mixed at 800 rpm for 35 minutes. The inner tube layer was extruded through an extruder at 183°C.

[0064] After checking the dimensions of the outer wear-resistant layer pipe and the inner pipe layer, put the outer wear-resistant layer pipe on the inner pipe layer body and put it into the heating device. The monitoring system controls the uniform heating and slowly raises the temperature to 165°C, applies a pressure of 1MPa to the pipe, and maintains the pressure and temperature for 15 minutes. The monitoring system operates as follows:

[0065] The temperature, pressure and dimension data are acquired through the acquisition module. A temperature sensor is installed in the heating device, a pressure sensor is installed at the point where the pipe pressure is applied, and a dimension measurement sensor is installed before and after the pipe is compounded. The data is transmitted to the data processing module.

[0066] The data processing module uses mean filtering and median filtering algorithms to process data and obtain preprocessed data. Check the difference between adjacent preprocessed data, mark the temperature data that exceeds the threshold, and verify the marked data by comparing with adjacent sensor data and historical data trend analysis. Abnormal data will not be processed.

[0067] The result data control module establishes a real-time database for temperature, pressure, and dimension data, and records the measured values ​​and timestamps. Calculate the difference between adjacent measured values, establish a trend model library, compare the real-time monitoring trend with the model library trend, calculate the difference between the actual temperature and 165°C, etc., and establish a deviation impact assessment model based on material properties and process requirements. Combined with abnormal data, statistically analyze the situation where the difference between adjacent data exceeds the threshold, and establish an abnormal data judgment rule library. Integrate the positive feedback trend deviation information and the negative feedback deviation and abnormal data information, calculate the evaluation value according to the weight, and make an early warning decision if the evaluation value reaches the early warning threshold.

[0068] After the compounding is completed, the product is naturally cooled to room temperature to obtain a wear-resistant PVC power pipe.

[0069] The strength and stability of the prepared power pipe were then tested. The results are shown in Table 1. The results show that its strength and stability are significantly improved compared to traditional PVC power pipes. The combination of filler and resin was observed by scanning electron microscopy, and it was found that the use of mixed silane coupling agent made the filler and resin tightly combined. The interface bonding strength between the filler and the resin was improved by about 50% compared to the traditional method.

[0070] During the processing, the thermal stability and the uniformity of the dispersion of the components were monitored. The results showed that the combination of calcium-zinc composite thermal stabilizer and mixed dispersant can effectively ensure the thermal stability and the uniformity of the dispersion of the components during the processing.

[0071] Table 1 Performance improvement index comparison table

[0072] Performance Indicators Control group Experimental Group in conclusion Tensile Strength 30MPa 40MPa [(40-30) / 30]×100%=33.3% Compressive strength 25MPa 32MPa [(32-25) / 25]×100%=28% Complex deformation 8mm 3mm [(8-3) / 8]×100%=62.5% Binding force 20N 30N [(30-20) / 20]×100%=50% Temperature fluctuations ±10℃ ±5℃ [(10-5) / 10]×100%=50% Composition uniformity 8% 3% [(8-3) / 8]×100%=62.5% Defect Rate 10% 7% [(10-7) / 10]×100%=30%

[0073] Example 2: On the basis of Example 1, take 16 parts of polyethylene, 62 parts of polyetheretherketone, 12 parts of polyurethane, 25 parts of a mixed fiber composed of basalt fiber, aramid fiber, glass fiber and carbon fiber in a ratio of 1:1:1:1, 12 parts of nano-boron nitride, 3.5 parts of silane coupling agent, 1.2 parts of graphite nanosheet lubricant, and 1.5 parts of calcium zinc stabilizer.

[0074] The inner tube layer includes the following components by weight: 82 parts of PVC resin, 16 parts of modified filler, 24 parts of ethylene-vinyl acetate copolymer, 3.5 parts of composite heat stabilizer, 2.2 parts of dispersant, 1.1 parts of lubricant, 4 parts of mixed silane coupling agent, 1.8 parts of plasticizer, 2.2 parts of antioxidant, 3.5 parts of compatibilizer and 6 parts of wear-resistant filler.

[0075] Subsequently, the prepared power pipe was subjected to wear resistance test, mechanical property test and chemical stability test, and the results are shown in Table 2, where:

[0076] The wear resistance test method is as follows: the prepared power pipe is tested for wear resistance using a wear testing machine. The results show that it has excellent wear resistance. After a certain period of wear, the amount of wear is much smaller than that of traditional PVC power pipes.

[0077] The test method of mechanical properties test is as follows: the power pipe is subjected to compression, tensile and bending performance tests. The results show that it has excellent mechanical properties, and the compressive strength, tensile strength and bending strength all meet the requirements of relevant standards, and it has strong impact resistance.

[0078] The test method of chemical stability test is as follows: After the power tube is immersed in acid, alkali and salt solution for a certain period of time, its appearance and performance changes are observed. The results show that the power tube can resist the erosion of acid, alkali, salt and other chemical substances, and its performance is stable without obvious corrosion.

[0079] Table 2 Comparison of characteristic advantage indicators

[0080] Performance Indicators Control group Experimental Group in conclusion Wear 10g 2g (2 / 10)×100%=20% Compression resistance standard 80% 120% [(120-80) / 80]×100%=50% Tensile standard 90% 130% [(130-90) / 90]×100%=44.4% Bending resistance standard 85% 125% [(125-85) / 85]×100%=47.1% Shock resistance 100J 140J [(140-100) / 100]×100%=40% Acid corrosion Corrosion none [(5-0) / 5]×100%=100% Alkali loss rate 3% 1% [(3-1) / 3]×100%=66.7% Salt performance degradation 15% 8% [(15-8) / 15]×100%=46.7%

[0081] Example 3: On the basis of Example 1, take 20 parts of polyethylene, 70 parts of polyetheretherketone, 20 parts of polyurethane, 25 parts of mixed fiber composed of basalt fiber, aramid fiber, glass fiber and carbon fiber in a ratio of 1:1:1:1, 15 parts of nano-boron nitride, 5 parts of silane coupling agent, 2 parts of graphite nanosheet lubricant, and 3 parts of calcium zinc stabilizer.

[0082] The inner tube layer includes the following components by weight: 90 parts of PVC resin, 20 parts of modified filler, 26 parts of ethylene-vinyl acetate copolymer, 4.5 parts of composite heat stabilizer, 3 parts of dispersant, 1.4 parts of lubricant, 5 parts of mixed silane coupling agent, 2.5 parts of plasticizer, 2.6 parts of antioxidant, 6 parts of compatibilizer and 8 parts of wear-resistant filler.

[0083] Subsequently, the process parameter control verification and monitoring system verification of the prepared power tube were carried out, and the results are shown in Table 3, where:

[0084] The temperature, time, speed and other parameters of each process step were accurately monitored. The results showed that the preparation method adopted can accurately control these parameters and ensure the stability of product quality. The temperature control accuracy is within ±3°C, the time control accuracy is within ±1 minute, and the speed control accuracy is within ±10 rpm.

[0085] The operating effect of the monitoring system was verified. The results showed that the monitoring system can accurately obtain data such as temperature, pressure, and size, and can effectively control and adjust according to the data, improving the accuracy and efficiency of the composite process. The accuracy of data acquisition reached more than 98%, and after adjustment according to the data, the efficiency of the composite process increased by about 30%.

[0086] Table 3 Comparison of technology innovation and application prospect indicators

[0087]

[0088]

[0089] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.

Claims

1. A wear-resistant PVC power pipe, characterized in that: The power pipe comprises an outer wear-resistant layer and an inner pipe layer, wherein the outer wear-resistant layer comprises the following components by weight: 15-20 parts of polyethylene, 60-70 parts of polyetheretherketone, 10-20 parts of polyurethane, 25-25 parts of mixed fiber, 12-15 parts of nano boron nitride, 3-5 parts of silane coupling agent, 1-2 parts of graphite nanosheet lubricant, and 1-3 parts of calcium zinc stabilizer; The inner tube layer comprises the following components by weight: 80-90 parts of PVC resin, 16-20 parts of modified filler, 24-26 parts of ethylene-vinyl acetate copolymer, 3-4.5 parts of composite heat stabilizer, 2-3 parts of dispersant, 1.1-1.4 parts of lubricant, 4-5 parts of mixed silane coupling agent, 1.5-2.5 parts of plasticizer, 2-2.6 parts of antioxidant, 3-6 parts of compatibilizer, and 6-8 parts of wear-resistant filler; The specific preparation method of the compatibilizer is as follows: Step A1: dissolve PVC in tetrahydrofuran, add the solution into a four-necked flask equipped with a stirring device, a thermometer, a reflux condenser and a nitrogen protection device, slowly add a mixture of styrene and acrylic acid into the four-necked flask, and stir evenly; Step A2: Add initiator BPO and antioxidant into a four-necked flask, raise the temperature to 70-90°C under nitrogen protection, and react for 3-5 hours; Step A3: After the reaction is completed, cool to room temperature, pour the product into methanol for precipitation, remove unreacted monomers, initiators and solvents, filter the precipitate, wash it repeatedly with methanol, and then dry it in a vacuum drying oven to constant weight to obtain a styrene-acrylic acid copolymer grafted polyvinyl chloride compatibilizer.

2. The wear-resistant PVC power pipe according to claim 1, characterized in that: The amount of the initiator BPO is 0.5%-2% of the total mass of PVC, styrene and acrylic acid, and the molar ratio of styrene to acrylic acid is 2:1-4:

1.

3. The wear-resistant PVC power pipe according to claim 1, characterized in that: The mixed silane coupling agent is prepared by mixing vinyl triethoxy silane coupling agent and gamma-aminopropyl triethoxy silane coupling agent in a ratio of 3:2, and the plasticizer is prepared by mixing epoxy soybean oil and dioctyl terephthalate in a ratio of 2:

1.

4. The wear-resistant PVC power pipe according to claim 1, characterized in that: The composite heat stabilizer is a calcium-zinc composite heat stabilizer, and the dispersant is a mixture of EBS and polyethylene wax in a ratio of 1:

1.

5. The wear-resistant PVC power pipe according to claim 1, characterized in that: The specific preparation method of the modified filler is as follows: Step B1: vacuum drying the nano boron nitride at 120°C for 10 hours, adding the silane coupling agent KH580 to a mixed solution of ethanol and water, wherein the volume ratio of ethanol to water is 9:1, adjusting the pH value of the solution to 5, and then stirring the reaction at 70°C for 2 hours; Step B2: adding the dried nano boron nitride to the hydrolyzed silane coupling agent solution, stirring and reacting at 80° C. for 6 hours; Step B3: Filter and wash the product after the reaction, and then vacuum dry it at 80° C. for 12 hours to obtain a modified filler after the nano-boron nitride is modified by a silane coupling agent.

6. A method for preparing a wear-resistant PVC power pipe, characterized in that: The method comprises the following preparation steps: Step S1: prepare the outer wear-resistant layer in advance, mix basalt fiber, aramid fiber, glass fiber and carbon fiber in proportion, put them into a vacuum drying oven, dry them at 90°C for 6 hours, put nano boron nitride into a vacuum drying oven at 135°C for 10 hours, and sieve polyethylene, polyetheretherketone and polyurethane respectively; Step S2: adding the treated polyethylene, polyetheretherketone, and polyurethane into a high-speed mixer, setting the speed to 650 rpm, mixing for 15 minutes, slowly adding the treated mixed fiber, nano boron nitride, silane coupling agent KH580, graphite nanosheet lubricant, and calcium zinc stabilizer, continuing to mix at a speed of 700-800 rpm for 30-45 minutes, and extruding using a twin-screw extruder at a temperature of 188° C.-228° C. to obtain an outer wear-resistant layer; Step S3: placing the PVC resin and ethylene-vinyl acetate copolymer in a drying oven and drying them at 70° C. for 5 hours, and drying the modified filler of nano-boron nitride modified by the silane coupling agent in a vacuum drying oven at 115° C. for 8 hours; Step S4: adding the dried PVC resin, ethylene-vinyl acetate copolymer, and modified filler into a high-speed mixer, mixing at a speed of 950 rpm for 20-25 minutes, adding a composite heat stabilizer, a dispersant, a lubricant, a mixed silane coupling agent, a plasticizer, an antioxidant, a compatibilizer, and a wear-resistant filler in sequence, and continuing to mix at a speed of 800 rpm for 35 minutes; Step S5: adding the mixed materials into an extruder at 168°C-198°C for extrusion to obtain an inner tube layer; Step S6: After the outer wear-resistant layer pipe and the inner pipe layer are extruded, cooled and sized, the outer wear-resistant layer pipe is put on the inner pipe layer body, and then the put-on pipe is placed in a heating device. The monitoring system controls the system to heat evenly and slowly raise the temperature to 165°C. A pressure of 0.8-1.2MPa is applied to the pipe, and the pressure and temperature are maintained for 15 minutes. After the compounding is completed, the pipe is taken out of the heating device and naturally cooled to room temperature to obtain a wear-resistant PVC power pipe.

7. The method for preparing a wear-resistant PVC power pipe according to claim 6, characterized in that The mixed fiber is composited by basalt fiber, aramid fiber, glass fiber and carbon fiber in the ratio of 1:1:1:

1.

8. The method for preparing a wear-resistant PVC electric power pipe according to claim 6, characterized in that: The specific monitoring method of the monitoring system in step S6 is as follows: Step 1: Obtain comprehensive data, including temperature, pressure, and dimension data, by setting up an acquisition module. By setting a temperature sensor in the heating device, a pressure sensor at the pipe pressure application point, and a dimension measurement sensor at the position before and after the pipe is compounded, the comprehensive data is obtained in real time and transmitted to the data processing module. Step 2: The data processing module performs noise processing and outlier analysis on the collected data to obtain preprocessed data, which is then marked and processed by the data processing module to obtain result data; Step 3: Use the result data control module to adjust the preparation process by establishing a real-time database and deviation impact assessment model while recording the management change trend of the comprehensive data.

9. The method for preparing a wear-resistant PVC electric power pipe according to claim 8, characterized in that: In step 3, the result data controls the control module, and the specific method of adjusting the preparation process is as follows: Step D1: The result data includes pre-processed data, marked data and abnormal data, and a real-time database is established for the temperature, pressure and size data in the comprehensive data; Step D2: continuously record the measured values ​​of the comprehensive data and calculate the difference between adjacent measured values; Step D3: Establish a trend model library to store typical trend models of comprehensive data changing over time during normal production; Step D4: Calculate the temperature difference, pressure difference range, and size design error range respectively, and compare them to get the deviation value. Combine the material property data and process requirement data to establish a deviation impact assessment model. Step D5: Combined with the abnormal data marked by the data processing module, statistical analysis is performed on the data whose adjacent data difference exceeds one times the threshold value, and an abnormal data determination rule base is established; Step D6: Fuse the positive feedback trend deviation information and the negative feedback deviation and abnormal data information to obtain fused data.

Citation Information

Patent Citations

  • High pressure and wear resistance PVC hose material and preparation method thereof

    CN105906980A

  • Preparation method of anti-corrosion pipe material

    CN108264706A

  • Composite electric power tube and preparation method thereof

    CN111600273A

  • Super-strong modified polyvinyl chloride power pipe and preparation method thereof

    CN111793296A

  • Low-dielectric-strength composite material for communication and preparation method thereof

    CN114031900A